Sports biomechanics analysis of wheelchair racing - Zheng, W.; Ma, Y.; Zhang, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Most of the research on wheelchair racing is in reference to the physiological and biochemical indices, but research based on sports biomechanics is scarce. To satisfy the need of the Chinese wheelchair racing teams, research based on the sport biomechanics of wheelchair racing was carried out. Findings from the study will contribute to the goal winning gold medals at the Beijing 2008 Olympic Games.